Deficient activation of CD95 (APO-1/ Fas )-mediated apoptosis: a potential factor of multidrug resistance in human renal cell carcinoma - Ramp, Uwe; Krammer, Peter H. (British journal of cancer, 2000)
The pronounced resistance of human renal cell carcinoma (RCC) to anticancer-induced apoptosis has primarily been related to the expression of P-glycoprotein and effective drug detoxification mechanisms. Because the CD95 system has recently been identified as a key mediator of anticancer drug-induced apoptosis, we analysed the contribution of the CD95 system to chemotherapy-induced apoptosis in four newly established RCC cell lines. Here, we demonstrate that all RCC cell lines expressed CD95-receptor and -ligand. Exposure to agonistic anti-CD95 antibodies resulted in induction of apoptosis and significant (P< 0.05) reduction of cell number in three out of four cell lines, indicating that the essential components for CD95-mediated apoptosis were present and functionally intact in the majority of these RCC cell lines. Moreover, treatment of cultures with bleomycin or topotecan, a novel topoisomerase I inhibitor with little substrate affinity for P-glycoprotein, led to induction of apoptosis and significant (P< 0.05) dose-dependent reduction of cell number in all RCC cell lines. Both anticancer drugs also induced upregulation of CD95 ligand expression in all cell lines. Additionally, augmentation of CD95 receptor expression was found in three RCC cell lines, including one p53-mutated cell line, whereas another p53-mutated cell line showed no or only a weak CD95 receptor upregulation after exposure to topotecan or bleomycin, respectively. Despite this upregulation of CD95 receptor and ligand, antagonistic antibodies directed against CD95 receptors or ligands could not inhibit induction of apoptosis by topotecan and bleomycin in any cell line. Thus, although a functionally intact CD95 signalling cascade is present in most RCC cell lines, the anticancer drugs topotecan and bleomycin that induce upregulation of CD95 receptor and ligand fail to effectively activate CD95-mediated apoptosis. This deficient activation of CD95-mediated apoptosis might be an important additional factor for the multidrug resistance phenotype of human RCCs. © 2000 Cancer Research Campaign